(untitled) (INNOTEC, 2013)
Atrazine is an herbicide used to control annual weeds and perennial grasses. Due to the toxicity of atrazine and its metabolites, this herbicide is banned in the European Union. In Uruguay atrazine is the second most frequently imported herbicide. It has been detected in surface water courses, particularly those that provide water for potabilization plants.The main mechanism for atrazine removal in neutral pH environments is the bacterial degradation. The microorganisms can degrade atrazine giving intermediates that vary in persistence and toxicity, or mineralize it giving ammonia and carbondioxide. The separation and detection of atrazine intermediates of biological degradation is important to know the potential of bacterial consortia to be applied in bioremediation processes. In this paper we developed an isocratic method of high performance liquid chromatography (HPLC) by ion-pair reversed phase to separate atrazine and metabolites in a synthetic culture medium. This method was useful to detect intermediates of atrazine degradation produced by selected native bacterial consortia. In addition, the method was employed to assess if atrazine adsorbed on activated carbon could be degraded by an active degrading consortium.